Using psychology in the classroom - Minton, Stephen James (Los Angeles : Sage, 2012)
Presents a guide for teachers on how to use psychological approaches in education, focusing on dealing with prejudice, stress and stress management, special educational needs, and other topics.
Includes bibliographical references and index.
Includes bibliographical references (p. 151-165) and index.
Professional.
Professional
Keywords: Educational psychology; Educational psychology